Effect of Sn nanoparticles on the optical properties of PEDOT:PSS thin films - Aly, Kamal A.; Ismail, Yasser A. M.; Salman S. Alsulami, Ziad; Abolibda, Tariq Z.; Almohammedi, Abdullah; Gomha, Sobhi M.; Ahmed, Hoda A.; Ibrahim, Mohamed S. (Frontiers in Physics, 2024)
Introduction: In this study, we focus on enhancing the optical properties of PEDOT:PSS thin films by incorporating pure Sn nanoparticles (NPs) synthesized using the ultrasonic ablation technique. The objective is to investigate the impact of Sn concentration on the optical characteristics of the films, with a specific emphasis on applications in organic solar cells. Methods: We systematically varied the concentrations of Sn in PEDOT:PSS thin films and characterized their optical properties. The index of refraction (n) and extinction coefficient (k) were precisely determined by analyzing the transmission and reflection spectra of the films. Additionally, Sellmeier’s dispersal model was employed to elucidate the obtained results of n, and dispersive factors were calculated and interpreted. Results: The incorporation of Sn nanoparticles led to improvements in the energy bandgap (Eg) values of PEDOT:PSS films. Notably, as the concentration of Sn increased, the n values decreased, indicating enhanced suitability for organic solar cell applications. The study also unveiled a decrease in the dielectric constant of PEDOT:PSS/Sn films with increasing Sn content, resulting in improved transmittance velocity and enhanced efficacy of microelectronic devices. This, in turn, promotes the development of large-frequency and large-velocity stretchy circuit boards. Discussion: The comprehensive assessment of optical and dielectric parameters, including complex dielectric constant, complex optical conductance, and nonlinear optical constants, provides valuable insights into the potential applications of PEDOT:PSS/Sn films. The larger nonlinear optical constants observed in the present films suggest their suitability for diverse applications such as all-optical switching, limiting, phase modulation, and frequency conversion. Overall, our findings highlight the promising potential of Sn-incorporated PEDOT:PSS thin films in advancing the field of optoelectronics and microelectronics.